Legislative Efforts to Address Dual Nationality: A Comparative Study in Iraqi and Jordanian Law - Alaa Farhan Abd Ali, Researcher; Bijan Haji Azizi, :Supervisor Professor; Mohammad Hassan Asadi, Supervisor. (lark, 2026)
abstractationality constitutes the fundamental legal and political bond linking an individual to the state. It serves as the determinant of their civil rights and obligations, and distinguishes their legal status from that of a foreigner. Nationality acquires its pivotal significance as the mechanism through which individuals are geographically allocated among states, and it acts as the conclusive reference point for designating the applicable law within the domain of conflict of laws. Therefore, it is imperative to regulate the basis for acquiring nationality according to precise and consistent standards to prevent disorder in both international and individual relations. However, the subjection of these foundations to the requirements of national legislative sovereignty, coupled with the limited influence of international law in overseeing this regulation, has resulted in a sharp divergence in the rules governing nationality across states. This disparity has led to the emergence of the phenomenon of dual nationality, which raises complex international legal issues and imposes challenges that significantly burden the affected individuals. In this study, we shall adopt a descriptive, analytical, and comparative methodology to deconstruct this phenomenon, outline its drawbacks, identify the factors contributing to its emergence, and explore methods for its combatment. The research will specifically focus on the contexts of Iraqi and Jordanian law and the legislative efforts in both countries to mitigate the complications arising from dual nationalityKeywords: citizenship, dual citizenship, citizen, foreigner.
Keywords: citizenship; dual citizenship; citizen